Pengaruh Konsentrasi GA3 Terhadap Induksi TunasTanaman Anggur (Vitis vinivera L.) Secara In Vitro - SONDANG RAJAGUKGUK; RINDANG DWIYANI; I NYOMAN GEDE ASTAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
The Effect of GA3 Concentration on The Induction of Grapevine (Vitis vinifera L.) Shoots Grown In Vitro The research concerning ‘The Effect of GA3 Concentration on the Induction of Grapevine (Vitis vinifera L.) Shoots Grown In Vitro’ have been conducted during period of February to August 2016 at The Laboratory of Plant Tissue Culture, Faculty of Agriculture, Udayana University. The objective of the research was to find out the most appropriate concentration of GA3 in stimulating of grapevine shoot grown in vitro. The experiment was laid out in a Completely Randomized Design with 5 treatments of GA3 concentration. The treatments were 0, 10, 20, 30, 40 ppm of GA3, each was replicated five times. The results showed that the treatment of 20 ppm GA3 was the most appropriate concentration in stimulating growth of grapevine shoots. The highest percentage of explants growing shoots i.e. 33.3% was obtained with the treatment of 20 ppm of GA3, compared to 6,6% (0 ppm), 0% (10 ppm), 20% (30 ppm), 6,6% (40 ppm).